Factors that influence the effectiveness of management by objectives with South African sales employees. - Pieters, Carike (My University, 2017)
This research investigates Management by Objectives (MBO) as a performance management system (PMS) used within the chemical manufacturing sector. Research has looked at the success and failure of the system; however, there were limited literature regarding the factors related to MBO and how they will impact on sales employees within the organisation. By identifying these factors, organisations can ascertain where their focus should be to improve their MBO and ultimately the performance of sales employees. This research study identified 13 factors that could influence the effectiveness of a programme like MBO on sales employees within the chemical manufacturing sector. Qualitative research was conducted and there after thematic content analysis was used to review and assess the data results obtained from the 15 semi-structured in-depth interviews with experienced sales employees. These interviews assisted the researcher to have a clear understanding of the factors that could influence MBO. From these 13 identified factors, ten were supported by the data as factors that could influence the effectiveness of MBO. The top three factors in order were: Employee behaviour directly related to employee engagement (Saks & Gruman, 2014); rewards and incentives as illustrated by Sharma (2013), and the degree of top level support which includes the full buy- in from management and support for employees to achieve the set goals (de Waal, 2007). Engaged employees and dedicated managers are of vital importance for a successful MBO. An organisation that wants to implement an effective MBO system and achieve the best possible results should consider the factors as laid out in the research and make sure they have a management team and leadership that are fully committed to the implementation thereof. Organisations should focus on keeping their employees fully engaged as employee engagement is a precursor for performance (Saks & Gruman, 2014).
MBA Thesis
Keywords: Management by objectives,Sales personnel -- South Africa.